2006
DOI: 10.1007/s10450-006-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Basic Blue 17 from aqueous solutions by using chemically crosslinked polyelectrolyte AAm/AASS hydrogels

Abstract: In this study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have been reported on the properties of hydrogels as a function of their ionic or hydrophilic group content [5][6][7][8][9][10][11] . Increasing number of ionic or hydrophilic groups in the hydrogels is known to increase their swelling capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the properties of hydrogels as a function of their ionic or hydrophilic group content [5][6][7][8][9][10][11] . Increasing number of ionic or hydrophilic groups in the hydrogels is known to increase their swelling capacity.…”
Section: Introductionmentioning
confidence: 99%